Application of Electric Propulsion for Low Earth Orbit Station Keeping. (2017) - Volotsuev, V.V.; Salmin, V.V.; Safronov, S.L.; Stratilatov, V.V.; Tkachenko, I.S.; Raube, S.S.; Shikhanov, S.V.; Shikhanova, E.G.
Abstract: This paper considers the problem of keeping a low Earth elliptical orbit of a satellite by low thrust electric propulsion. The main disturbance is the aerodynamic drag. Its precise value is not known well enough. Suggested correction algorithms imply: 1) stepwise verification of the perturbation force by direct measurement; and 2) calculation of control parameters by approximate analytical relations. Results of modeling the processes of satellite motion control are given.